Application of Liquid Fertilizer Trichoderma harzianum (R3) on Siam Citrus (Citrus nobilis var. microcarpa) - Asiah, Nur; Rahmawati, Rahmawati; Mukarlina, Mukarlina; Khotimah, Siti (Jurnal Biologi Tropis, 2025)
An economically significant fruit in West Kalimantan is the Siam orange (Citrus nobilis var. microcarpa). Low fertility is a problem for Siam orange cultivation in the region's vast peatlands; Trichoderma sp. fertilizer can promote organic matter breakdown, increase nutrient availability, and aid in plant growth. This study aimed to evaluated the effect of liquid T. harzianum (R3) on Siam orange seedlings in peat soil. The study employed a completely randomized design (CRD) with four replications for each of the five treatments: control (0), 5, 15, 25, and 35 mL/L of T. harzianum (R3). Plant height, leaf count, root length, wet weight, dry weight, and chlorophyll content (a, b, and total) were among the parameters that were measured. The application of liquid T. harzianum (R3) had a significant impact on all growth metrics, including chlorophyll a and total chlorophyll content, according to the analysis of variance test. The most effective method for promoting the growth of siam orange seedlings was the application of 25 mL/L of liquid T. harzianum (R3).